2018
DOI: 10.1111/jfpp.13595
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the composition of tomato powder (Lycopersicon esculentum Mill) resulting from different drying methods

Abstract: Heating drying processes may cause undesirable changes in tomato composition and loss of quality, mainly in bioactive components. The objective of the study was to evaluate the effects of oven drying, heated air flow, and freeze‐drying on blanched and unblanched tomatoes. This allows choosing drying conditions with less undesirable changes. The contents of sugar, citric acid, ascorbic acid, lycopene, β‐carotene, and total phenolic compounds, and 5‐hydroxy‐2‐furaldehyde (HMF) formation were evaluated. Results r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In addition, the freeze-dried material was characterized by lower moisture content in comparison to unblanched pumpkin. Jorge et al [48] carried out water blanching of tomato before FD and found that blanching increased the content of phenolics, lycopene and β-carotene but decreased the content of ascorbic acid and sugars. Contrary to this report, Krzykowski et al [51] observed that water blanching and microwave blanching of red pepper slightly but significantly reduced the total phenolic content and antioxidant activity of dried and powdered pepper.…”
Section: Blanchingmentioning
confidence: 99%
“…In addition, the freeze-dried material was characterized by lower moisture content in comparison to unblanched pumpkin. Jorge et al [48] carried out water blanching of tomato before FD and found that blanching increased the content of phenolics, lycopene and β-carotene but decreased the content of ascorbic acid and sugars. Contrary to this report, Krzykowski et al [51] observed that water blanching and microwave blanching of red pepper slightly but significantly reduced the total phenolic content and antioxidant activity of dried and powdered pepper.…”
Section: Blanchingmentioning
confidence: 99%
“…The texture of strawberries changes during storage due to moisture evaporation (Asioli et al, 2018). If the moisture content in the cell decreases, the cell becomes soft and weak (Jorge et al, 2018).…”
Section: Texture Determinationmentioning
confidence: 99%
“…For example, tomato powder is usually used as a material with remarkable effects in some scientific studies [ 18 ]. β-carotene and LYC are the carotenoids that are often of concern in studies related to tomato powder drying [ 19 , 20 ]. Several studies have found an increase in β-carotene and LYC content in tomato products after drying treatment compared to fresh tomatoes, and have recognized that this proportion of increase is due to changes in extractability [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…β-carotene and LYC are the carotenoids that are often of concern in studies related to tomato powder drying [ 19 , 20 ]. Several studies have found an increase in β-carotene and LYC content in tomato products after drying treatment compared to fresh tomatoes, and have recognized that this proportion of increase is due to changes in extractability [ 20 ]. However, some studies have found that different conditions and parameters used in drying treatments may lead to different levels of LYC degradation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%